Development of STEM-Based e-Worksheets to Improve Creative Thinking Ability on the Topics of Angles - Wulanningtyas, Melania Eva; Ratnasari, Arshita Setya (Jurnal Pendidikan MIPA, 2022)
This research aims to develop e-worksheet learning media with a STEM approach to improve junior high school students' creative thinking skills. This research is a development research using the ADDIE model. This research was conducted at 6 Catholic private junior high schools in seventh grade. The results of this study are e-worksheets that are made to meet valid, practical, and effective aspect categories. Valid aspects are obtained through the assessment of material experts and media experts with values of 77 and 63.5 and fall into the very good and good categories. The practicality aspect was obtained through small-scale tests and large-scale tests with values of 80.17 and 75.83 and were in the good category for both. The effectiveness aspect is obtained through the results of the effectiveness test which includes paired sample ttest, one sample t-test, and mean different test. Based on the paired sample t-test for the experimental class and the control class, the results showed that there was an increase in scores before using the e-worksheet and after using the e-worksheet. Based on the one sample t-test, it was found that there was an increase in students' creative thinking abilities by using eworksheets. The conclusion of this study is that e-worksheets with the STEM approach are effective for improving junior high school students' creative thinking abilities.    Keywords: ADDIE, creative thinking, e-worksheet, STEM. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1680-1691